2011
DOI: 10.1007/s00701-011-1203-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines as markers of local inflammation and angiogenesis in patients with chronic subdural hematoma: a prospective study

Abstract: Chemokines are elevated in the hematoma cavity of patients with CSDH. It is likely that these signaling modulators play an important role in promoting local inflammation. Furthermore, biological activity of CCL2 and CXCL8 may promote neovascularization within the outer CSDH membrane, and a compensatory angiostatic activity of CXCL9 and CXCL10 may contribute to repairing this disorder. This phenomenon was restricted to the hematoma site, and the systemic chemokine levels might not reflect local immune responses. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…It is difficult to know the relevance of each individual cytokine as it is well recognised that they work in cascades, influence one another, can compete for receptors and act antagonistically or synergistically. A gross analysis of pro- and anti-inflammatory cytokines in CSDH shows they are both raised in CSDH fluid compared with serum, but that the balance is significantly more pro- than anti-inflammatory [61, 62]. It is important to consider the balance of both the pro- and anti-inflammatory molecules and how this changes over time.…”
Section: Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to know the relevance of each individual cytokine as it is well recognised that they work in cascades, influence one another, can compete for receptors and act antagonistically or synergistically. A gross analysis of pro- and anti-inflammatory cytokines in CSDH shows they are both raised in CSDH fluid compared with serum, but that the balance is significantly more pro- than anti-inflammatory [61, 62]. It is important to consider the balance of both the pro- and anti-inflammatory molecules and how this changes over time.…”
Section: Inflammationmentioning
confidence: 99%
“…Both IL-6 and IL-8 have been identified as being significantly elevated in CSDH fluid [53, 61, 73, 74, 80]. More significantly, high levels of these cytokines have been correlated with increased risk of CSDH recurrence and the related imaging features of recurrence [53, 73].…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar imbalance between anti- and pro-inflammatory molecules has been found in the CSDH fluid and this imbalance could influence the vascular permeability of the hematoma neomembrane and angiogenesis [7, 8, 44, 45]. Recent reports revealed that inflammatory factors, such as TNF-α, IL-6 and IL-10 are highly expressed in the hematoma fluid of patients with CSDH [44, 46].…”
Section: Introductionmentioning
confidence: 80%
“…Some studies of intracranial chronic subdural hematoma found an association with various factors including vascular endothelial growth factor, basic fibroblast growth factor, chemokines, and cytokines. [23][24][25] By clarifying the mechanisms of subdural hematoma formation, we may be able to develop innovative treatments that can prevent chronic hematoma formation and promote tissue healing responses to absorb hematomas within the acute phase.…”
Section: Discussionmentioning
confidence: 99%